Comprehensive diagnostic and therapeutic approaches to uterine teratoma in postmenopausal women: a case study and review - Pan, Wenwei; Lan, Jun; Tang, Zihao; Li, Taikang; Ma, Xinping (Frontiers in Oncology, 2024)
Background and objectiveUterine teratomas are extremely rare in postmenopausal women and pose significant challenges in diagnosis and treatment. This study reports a case of a 54-year-old postmenopausal woman diagnosed with a uterine teratoma during a routine gynecological ultrasound. The study aims to explore the diagnosis and treatment of uterine teratomas in postmenopausal women through detailed imaging assessment and hysteroscopy surgery, aiming to enhance the understanding of this rare uterine tumor and improve patient treatment outcomes and quality of life.MethodsThis study utilized hysteroscopic surgery to excise a mass initially suspected to be a uterine fibroid and performed pathological analysis. The analysis revealed the presence of fat and hair, confirming the diagnosis of a mature benign uterine teratoma. Additionally, the study includes a literature review summarizing the clinical characteristics, diagnostic methods, and treatment strategies for uterine teratomas.ResultsHysteroscopic surgery effectively identified and removed the complex uterine teratoma. Pathological analysis confirmed the teratoma contained various mature tissues, including neural tissue, bone, and cartilage. Comparative analysis of imaging features with surgical outcomes helped propose more precise diagnostic criteria and treatment guidelines.ConclusionHysteroscopy surgery plays a crucial role in diagnosing uterine teratomas in postmenopausal women and showcases its advantages of minimal trauma and quick recovery in treatment. In addition, the literature review emphasizes the diagnostic challenges of uterine teratomas in clinical practice, particularly in expanding clinical awareness of the differences between premenopausal and postmenopausal presentations. It also summarizes the diagnostic and treatment strategies for rare uterine masses, contributing to the improved recognition of these rare cases.